2010
DOI: 10.1182/blood-2009-08-236588
|View full text |Cite
|
Sign up to set email alerts
|

The impact on outcome of the addition of all-trans retinoic acid to intensive chemotherapy in younger patients with nonacute promyelocytic acute myeloid leukemia: overall results and results in genotypic subgroups defined by mutations in NPM1, FLT3, and CEBPA

Abstract: We investigated the benefit of adding all-trans retinoic acid (ATRA) to chemotherapy for younger patients with nonacute promyelocytic acute myeloid leukemia and high-risk myelodysplastic syndrome, and considered interactions between treatment and molecular markers. Overall, 1075 patients less than 60 years of age were randomized to receive or not receive ATRA in addition to daunorubicin/Ara-C/thioguanine chemotherapy with Ara-C at standard or double standard dose. There were data on FLT3 internal tandem duplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 21 publications
3
82
2
1
Order By: Relevance
“…(Levis, et al 2002, Metzelder, et al 2009, Stone, et al 2005, Zhang, et al 2008 An ongoing international intergroup trial (10603 RATIFY), incorporating midostaurin into induction, consolidation or maintenance setting is currently underway. All-trans retinoic acid in combination with chemotherapy was found to be beneficial for NPM1-mutated patients (Burnett, et al 2010); however this preliminary result was not confirmed by the other study done on younger patients. (Schlenk, et al 2009) Tyrosine kinase inhibitor, such as imatinib, might be of clinical value in treatment of patients with KIT mutations.…”
Section: Risk-adapted Treatment According To Gene Mutations In Aml Pacontrasting
confidence: 57%
“…(Levis, et al 2002, Metzelder, et al 2009, Stone, et al 2005, Zhang, et al 2008 An ongoing international intergroup trial (10603 RATIFY), incorporating midostaurin into induction, consolidation or maintenance setting is currently underway. All-trans retinoic acid in combination with chemotherapy was found to be beneficial for NPM1-mutated patients (Burnett, et al 2010); however this preliminary result was not confirmed by the other study done on younger patients. (Schlenk, et al 2009) Tyrosine kinase inhibitor, such as imatinib, might be of clinical value in treatment of patients with KIT mutations.…”
Section: Risk-adapted Treatment According To Gene Mutations In Aml Pacontrasting
confidence: 57%
“…These data were, however, not confirmed when studying younger patients (Burnett et al, 2009). The molecular basis of this response remains elusive, but it may correlate with the reported role of NPM as co-repressor of AP2a during retinoic acid-induced differentiation, including the NPM1 promoter itself (Liu et al, 2007a).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 84%
“…Germline CEBPA mutations were verified in affected individuals from pedigrees A to E, using bidirectional sequencing as previously described. 18 The sources of germline (constitutional) DNA included peripheral blood (PB) or bone marrow (BM) during remission (A. The index case in pedigree C was C.III.1, who presented in 2012 at 18 years of age.…”
Section: Familial Aml Patientsmentioning
confidence: 99%